Managing standardize memorizations strategy in tahfiz centres: a guideline for quality performance in Qur'anic memorization - Mustaffa, Muhaidi; Md Sawari, Siti Salwa (EduPedia Publications Pvt Ltd, 2018)
At present, numerous Tahfiz centres have been developed in Malaysia. Indeed, the increase of huffaz can be observed. However, the quality of huffaz memorization is still being questioned, a study has shown that numbers of huffaz feel unsure with their memorization. One of the main factors lead to this circumstance is lack of good management strategy in the Tahfiz centres. Thus, there is a need to standardize managing strategy indicators for memorizing Qur’an among all Tahfiz centres. The purpose of this study is to provide standardized managing strategy that can be implemented to all Tahfiz centres in memorizing Qur’an. Method used in this study is literature searches, numerous studies related the memorization strategies were combined and analyze. From the review analysis, it has been found that a good management in huffaz process must full fill four strategies; Purifying intentions, Talaqqi, Musyafahah, and memorizing in mind and writing. As conclusion it is hope that this standard can be used to monitor the status of the Tahfiz educational system and to track how it changes over time .